Fasting reduces the number of TRH immunoreactive neurons in the hypothalamic paraventricular nucleus of male rats, but not in mice. (1st May 2021) - Campos, Ana M.P.; Wasinski, Frederick; Klein, Marianne O.; Bittencourt, Jackson C.; Metzger, Martin; Donato, Jose
Graphical abstract: Highlights: Leptin induces pSTAT3 in PVH TRH neurons of rats, but not in mice. Fasting reduces the number of PVH TRH immunoreactive neurons of rats, but not in mice. Leptin deficient mice display reduced T4 levels, but normal number of PVH TRH neurons. Abstract: During fasting or weight loss, the fall in leptin levels leads to suppression of thyrotropin-releasing hormone (TRH) expression in the paraventricular nucleus of the hypothalamus (PVH) and, consequently, inhibition of the hypothalamic-pituitary-thyroid (HPT) axis. However, differently than rats, just few PVH TRH neurons express the leptin receptor in mice. In the present study, male adult rats and mice were submitted to 48 -h fasting to evaluate the consequences on proTRH peptide expression at the PVH level. Additionally, the proTRH peptide expression was also assessed in the brains of leptin-deficient ( Lep ob/ob ) mice. We observed that approximately 50 % of PVH TRH neurons of leptin-injected rats exhibited phosphorylation of the signal transducer and activator of transcription 3 (pSTAT3), a marker of leptin receptor activation. In contrast, very few PVH TRH neurons of leptin-injected mice exhibited pSTAT3. Rats submitted to 48 -h fasting showed a significant reduction in the number of PVH TRH immunoreactive neurons, as compared to fed rats. On the other hand, no changes in the number of PVH TRH immunoreactive neurons were observed between fasted and fed mice. Next, the number of TRH immunoreactive cells was determined in the PVH, dorsomedial nucleus of the hypothalamus and nucleus raphe pallidus of Lep ob/ob and wild-type mice and no significant differences were observed, despite reduced plasma T4 levels in Lep ob/ob mice. Taken together, these findings provide additional evidence of the important species-specific differences in the mechanisms used by fasting and/or leptin to regulate the HPT axis.